PR1‐mediated defence via C‐terminal peptide release is targeted by a fungal pathogen effector. Issue 6 (3rd January 2021) - Sung, Yi‐Chang; Outram, Megan A.; Breen, Susan; Wang, Chen; Dagvadorj, Bayantes; Winterberg, Britta; Kobe, Bostjan; Williams, Simon J.; Solomon, Peter S.
Summary: The effector SnTox3 from Parastagonospora nodorum elicits a strong necrotic response in susceptible wheat and also interacts with wheat pathogenesis‐related protein 1 (TaPR‐1), although the function of this interaction in disease is unclear. Here, we dissect TaPR1 function by studying SnTox3–TaPR1 interaction and demonstrate the dual functionality of SnTox3. We utilized site‐directed mutagenesis to identify an SnTox3 variant, SnTox3 P173S, that was unable to interact with TaPR1 in yeast‐two‐hybrid assays. Additionally, using recombinant proteins we established a novel protein‐mediated phenotyping assay allowing functional studies to be undertaken in wheat. Wheat leaves infiltrated with TaPR1 proteins showed significantly less disease compared to control leaves, correlating with a strong increase in defence gene expression. This activity was dependent on release of the TaCAPE1 peptide embedded within TaPR1 by an unidentified serine protease. The priming activity of TaPR1 was compromised by SnTox3 but not the noninteracting variant SnTox3 P173S, and we demonstrate that SnTox3 prevents TaCAPE1 release from TaPR1 in vitro . SnTox3 independently functions to induce necrosis through recognition by Snn3 and also suppresses host defence through a direct interaction with TaPR1 proteins. Importantly, this study also advances our understanding of the role of PR1 proteins in host–microbe interactions as inducers of host defence signalling.